Affirmative governmentality and the politics of youth inclusion: A critical analysis of youth voice and engagement in dominant political discourse in Ontario - Bernard, Maria (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2016)
While a robust literature tracks the ways in which racialized youth are excluded from dominant spaces, this article examines the effects of policies and programs that invite them in. The growing interest in youth inclusion and participation can be linked to key global influences such as the increasing shift towards asset-based and Positive Youth Development (PYD) models, that currently influences government policy and funding strategies in Canada and other countries. Using Foucault’s governmentality framework, I engage in a brief examination of Ontario’s document, Stepping Up: A Strategic Framework to Help Ontario’s Youth Succeed (2013), to understand how youth inclusion, participation, and civic engagement are imagined. This article seeks to disturb current constructs of marginalized youth voice and inclusion within dominant discourse in Canada and argues that these discourses function as a form of affirmative governmentality. I discuss the conditions of meaningful youth inclusion and participation, which requires questioning normative constructs of youth, acknowledging the structural oppressions experienced by young people, and working with youth to understand their own notions of participation. La gouvernementalité positive et les politiques d’inclusion des jeunes: Une analyse critique de la voix et l’engagement politique des jeunes dans le discours politique dominant en Ontario. Résumé Bien qu’il existe déjà beaucoup de données sur les manières dont les jeunes racialisés sont exclus des espaces dominants, cet article se penche sur les effets des politiques et programmes qui veulent les inclure. L’intérêt croissant pour la participation et l’inclusion des jeunes est peut-être lié à des influences globales majeures, comme le virement vers des modèles tels le développement fondé sur les acquis et le développement positif des jeunes, qui présentement à beaucoup d’influence sur les politiques et le financement gouvernemental au Canada et ailleurs. Utilisant le concept de gouvernementalité de Foucault, j’examine le document de l’Ontario Stepping Up: A Strategic Framework to Help Ontario’s Youth Succeed (2013), afin de comprendre comment l’inclusion, la participation, et l’engagement civique des jeunes, sont imaginés. Cet article veut troubler les constructions courantes de la voix et de l’inclusion des jeunes marginalisés dans les discours dominants au Canada. Je propose que ces discours servent en tant que gouvernementalité positive. Je discute des conditions qui créent une inclusion et une participation véritables des jeunes, ce qui exige questionner les constructions normative de la jeunesse, tout en reconnaissant que les oppressions structurelles auxquelles les jeunes font face, et travailler a comprendre leurs propres notions de participation. Mots clefs: participation et inclusion des jeunes; gouvernementalité; politiques des jeunes